Pengaruh Penambahan Timah Hitam (Pb) Pada Paduan High-Tin Bronze Terhadap Kekerasan - Suarjaya, I Gede; Sugita, I Ketut Gede; Negara, DNK Putra (Teknik Desain Mekanika, 2024)
Abstractt High-tin bronze, containing 80% copper (Cu) and 20% tin (Sn), is used in musical instruments such as bells and gamelan. This alloy is stable at room temperature and has good acoustic properties, meaning it can produce a high-pitched but brittle sound. The effort that can be exerted to increase the hardness of high-tin bronze alloys is given through the addition of lead (Pb). In this study, the casting process of High-Tin Bronze alloy was carried out with the addition of lead (Pb) with variations of 10%, 15%, and 20% at a pour temperature of 950 °C. The results of the Vickers test showed that the hardness of high-tin bronze increased with increasing concentrations of lead (Pb). The strongest value is found in high-tin bronze alloy 80% + Pb alloy 20% with an average hardness value of 224.19 VHN. While the lowest value was obtained in high-tin bronze alloy without the addition of lead (Pb) with an average hardness value of 202.42 VHN. Keywords : high-tin bronze, lead, hardness